Nitrogen and sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite as well as preparation method and application thereof
Modification of porous iron oxide/phosphide heterojunction nanocomposites by co-doping graphene by nitrogen and sulfur, the problem of scarce resources and high cost of precious metal-based electrocatalysts is solved, and the electrochemical activity and stability of water oxidation electrocatalysts is significantly improved. , optimized water oxidation reaction performance.
Patent Information
- Application Number
- CN202411448971.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
Due to scarce resources and high costs, existing precious metal-based electrocatalysts are difficult to produce on a large scale, and the application performance of alternative electrocatalysts needs to be optimized, especially in water oxidation reactions (OER).
The porous iron oxide/phosphide heterojunction nanocomposite is modified with nitrogen and sulfur co-doped graphene as the water oxidation electrocatalyst. The material is prepared by solvothermal reaction and solid phosphating reaction, and the electrochemistry is enhanced by its unique structural characteristics. Activity and stability.
It significantly improves the electrochemical activity and stability of the electrocatalyst, reduces the electrocatalytic impedance, enhances the carrier migration ability, optimizes the reaction activity and the adsorption path of the intermediate, and improves the water oxidation performance and practical application ability.
Smart Images

Figure CN119287435A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material and a preparation method and application thereof. Background Art
[0002] With the shortage of traditional fossil fuels, researchers are vigorously exploring clean and sustainable energy solutions. Hydrogen, as a clean alternative energy carrier, has attracted widespread attention from researchers due to its environmentally friendly characteristics and zero carbon emissions. Electrochemical water splitting is considered to be a promising and feasible strategy for large-scale hydrogen production due to its simple development process, low pollution, and superiority over other methods such as coal gasification and methane distillation modification.
[0003] Electrochemical water splitting consists of two opposing chemical reactions: the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). In order to achieve efficient water splitting, it is crucial to develop electrocatalysts with excellent performance. Such electrocatalysts can significantly improve reaction kinetics, reduce overpotentials and enhance stability. The most widely used OER electrocatalysts are precious metal-based electrocatalysts, such as platinum (Pt), rubidium (Ru), iridium (Ir), Pt / C, RuO2 and IrO2. However, the large-scale production of the above-mentioned precious metal-based electrocatalysts is severely restricted due to resource scarcity and high cost. Therefore, the development of alternative electrocatalysts with excellent OER performance has gradually become a mainstream research direction. At present, alternative materials have been designed as economically viable electrocatalysts, including oxides, sulfides, selenides, nitrides, carbides and phosphates, which are abundant in reserves and inexpensive. However, although researchers have designed economically viable electrocatalysts, the actual application performance of the above-mentioned electrocatalysts compared with precious metal-based catalysts still needs to be further optimized. Summary of the invention
[0004] The object of the present invention is to provide a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material and a preparation method and application thereof. The nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material has excellent electrochemical activity and kinetics as a water oxidation electrocatalyst.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a nitrogen-sulfur co-doped graphene-modified porous iron oxide / phosphide heterojunction nanocomposite material, comprising the following steps:
[0007] (1) mixing an iron source, an alkaline salt and an organic solvent to perform a solvothermal reaction to obtain porous Fe3O4 nanospheres;
[0008] (2) mixing and dispersing the porous Fe3O4 nanospheres, nitrogen-sulfur co-doped graphene, surfactant and water described in step (1); annealing the mixed and dispersed product under a protective atmosphere to obtain a nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material;
[0009] (3) Under a protective atmosphere, subjecting the nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material described in step (2) to a solid-state phosphating reaction with a phosphorus source to obtain a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material.
[0010] Preferably, in the preparation method, in step (1), the iron source includes ferric chloride and / or ferric nitrate; the alkaline salt includes one or more of sodium acetate, sodium carbonate and sodium citrate; the organic solvent is a mixture of ethylene glycol and diethylene glycol, and the volume ratio of ethylene glycol to diethylene glycol is 0.5-2:2-8.
[0011] Preferably, in the preparation method, in step (1), the molar ratio of the iron source to the alkaline salt is 0.5-2:4.4-17.6, and the molar to volume ratio of the iron source to the organic solvent is 0.5-2 mmol:5-20 mL.
[0012] Preferably, in the preparation method, in step (1), the temperature of the solvent thermal reaction is 150 to 240° C., and the time is 4 to 16 hours.
[0013] Preferably, in the preparation method, in step (2), the surfactant includes hexadecyltrimethylammonium bromide and / or polyvinyl pyrrolidone; the mass ratio of the porous Fe3O4 nanospheres, the nitrogen-sulfur co-doped graphene and the surfactant is 9-36:12.5-50:0.5-2.
[0014] Preferably, in the preparation method, in step (2), the annealing treatment is performed at a temperature of 350 to 1200° C. and for a time of 0.5 to 4 hours.
[0015] Preferably, in the preparation method, in step (3), the phosphorus source includes sodium hypophosphite and / or ammonium hypophosphite; and the mass ratio of the nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material to the phosphorus source is 0.5-2:3-15.
[0016] Preferably, in the preparation method, in step (3), the temperature of the solid-state phosphating reaction is 270-450° C., the time is 1-4 hours, and the rate of heating to the desired solid-state phosphating reaction temperature is 1-10° C. / min.
[0017] The present invention also provides a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material prepared by the preparation method.
[0018] The present invention also provides an application of the nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material as a water oxidation electrocatalyst.
[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The porous Fe3O4 / FeP heterojunction small-sized nanospheres prepared by the present invention as a highly efficient water oxidation electrocatalyst exhibit excellent electrochemical activity and stability mainly due to the following reasons:
[0021] ① The porous Fe3O4 / FeP heterojunction small-sized nanospheres modified by nitrogen-sulfur co-doped graphene exhibit low electrocatalytic impedance. The porous distribution on the nanospheres increases the infiltration of electrolyte ions and the transfer of electrons in the catalyst, accelerates the interaction between electrons and protons, and increases the rapid release of gas, thereby improving the electrochemical performance;
[0022] ② The synergistic effect of nitrogen-sulfur co-doped hybrid graphene and Fe3O4 / FeP heterostructure interface enhances the migration of carriers and overcomes the strong corrosion of the electrolyte, thereby significantly improving the reaction activity and stability in the OER process, while also providing help for the exposure of active sites and optimizing the adsorption path of reaction intermediates;
[0023] ③ The formation of Fe3O4 / FeP heterojunctional interface elements can promote fast charge transfer, interface structure stability, and the introduction of nitrogen-sulfur co-doped graphene with rich defects, thereby effectively exposing active sites, optimizing the adsorption energy barrier of the heterojunction on the electrocatalytic intermediates, and improving the electrocatalytic activity and stability;
[0024] ④ The Fe3O4 / FeP heterostructure with rich and heterogeneous interfaces can effectively regulate the electronic structure generated by strong interactions to help expose abundant electroactive sites and optimize the adsorption free energy of intermediates in the OER process, thereby improving the catalytic water oxidation performance and enhancing its practical application capabilities;
[0025] (2) The preparation method of the present invention is an integrated preparation process with low cost and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.
[0027] Figure 1TEM images of p-Fe3O4 and p-Fe3O4 / FeP@N,S-Gr of Example 1, wherein a is p-Fe3O4, and b and c are p-Fe3O4 / FeP@N,S-Gr;
[0028] Figure 2 is the XRD pattern of p-Fe3O4 / FeP@N,S-Gr of Example 1;
[0029] Figure 3 The performance comparison test results of p-Fe3O4, p-Fe3O4@N,S-Gr, p-Fe3O4 / FeP@N,S-Gr and RuO2 in Example 1, where a is the OER polarization curve and b is the performance comparison test results of p-Fe3O4, p-Fe3O4@N,S-Gr, p-Fe3O4 / FeP@N,S-Gr and RuO2 in Example 1, where a is the OER polarization curve and b is the performance comparison test results of p-Fe3O4, p-Fe3O4@N,S-Gr and ... 2 The overpotential is , c is the Tafel slope;
[0030] Figure 4 The electrochemical impedance of p-Fe3O4, p-Fe3O4@N,S-Gr, and p-Fe3O4 / FeP@N,S-Gr of Example 1;
[0031] Figure 5 This is a theoretical simulation of how the delocalization of charge distribution at the Fe3O4 / FeP heterojunction interface in Example 1 significantly enhances catalyst activity and conductivity. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing a nitrogen-sulfur co-doped graphene-modified porous iron oxide / phosphide heterojunction nanocomposite material, comprising the following steps:
[0033] (1) mixing an iron source, an alkaline salt and an organic solvent to perform a solvothermal reaction to obtain porous Fe3O4 nanospheres;
[0034] (2) mixing and dispersing the porous Fe3O4 nanospheres, nitrogen-sulfur co-doped graphene, surfactant and water described in step (1); annealing the mixed and dispersed product under a protective atmosphere to obtain a nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material;
[0035] (3) Under a protective atmosphere, subjecting the nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material described in step (2) to a solid-state phosphating reaction with a phosphorus source to obtain a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material.
[0036] In the present invention, the iron source in step (1) preferably includes ferric chloride and / or ferric nitrate, and more preferably ferric chloride.
[0037] In the present invention, the alkaline salt in step (1) preferably includes one or more of sodium acetate, sodium carbonate and sodium citrate, and further preferably includes sodium acetate, sodium carbonate or sodium citrate, and more preferably sodium acetate. The main function of the alkaline salt is to provide hydroxide ions and adjust the acidity and alkalinity of the reaction process.
[0038] In the present invention, the organic solvent in step (1) is preferably a mixture of ethylene glycol and diethylene glycol.
[0039] In the present invention, the volume ratio of the ethylene glycol to the diethylene glycol is preferably 0.5-2:2-8, more preferably 0.8-1.5:3-6, and even more preferably 1:4.
[0040] In the present invention, the molar ratio of the iron source to the alkaline salt in step (1) is preferably 0.5-2:4.4-17.6, more preferably 0.8-1.5:7-13.2, and more preferably 1:8.8.
[0041] In the present invention, the molar to volume ratio of the iron source to the organic solvent in step (1) is preferably 0.5-2 mmol:5-20 mL, more preferably 0.8-1.5 mmol:8-15 mL, and more preferably 1 mmol:10 mL.
[0042] In the present invention, the time for mixing the iron source, alkaline salt and organic solvent in step (1) is preferably 0.5 to 4 hours, more preferably 1 to 3 hours, and more preferably 2 hours.
[0043] In the present invention, the temperature of the solvent thermal reaction in step (1) is preferably 150-240°C, more preferably 180-220°C, and more preferably 200°C; the time is preferably 4-16h, more preferably 6-10h, and more preferably 8h.
[0044] In the present invention, after the solvothermal reaction in step (1), preferably washing with ethanol and water is also included in sequence.
[0045] In the present invention, the number of washing with ethanol and the number of washing with water are independently preferably 2 to 10 times, more preferably 4 to 8 times, and even more preferably 5 times.
[0046] In the present invention, the specific method of mixing and dispersing the porous Fe3O4 nanospheres, nitrogen-sulfur co-doped graphene, surfactant and water in step (2) preferably includes the following steps: mixing and dispersing the porous Fe3O4 nanospheres with water to obtain a first dispersion; mixing and dispersing the nitrogen-sulfur co-doped graphene with water to obtain a second dispersion; mixing and dispersing the surfactant with water to obtain a third dispersion; and sequentially adding the second dispersion and the third dispersion into the first dispersion for dispersion.
[0047] In the present invention, in the first dispersion, the mass-to-volume ratio of porous Fe3O4 nanospheres to water is preferably 3-30 mg: 5-50 mL, more preferably 8-20 mg: 8-30 mL, and more preferably 9 mg: 10 mL.
[0048] In the present invention, in the second dispersion, the mass-to-volume ratio of nitrogen-sulfur co-doped graphene to water is preferably 1-10 mg:1-15 mL, more preferably 4-8 mg:2-10 mL, and more preferably 5 mg:6 mL.
[0049] In the present invention, in the third dispersion, the mass-to-volume ratio of the surfactant to water is preferably 0.2-4 mg:1-20 mL, more preferably 0.5-2 mg:2-10 mL, and even more preferably 1 mg:5 mL.
[0050] In the present invention, the time for mixing and dispersing the porous Fe3O4 nanospheres and water, and the time for mixing and dispersing the nitrogen-sulfur co-doped graphene and water is independently preferably 0.5 to 4 hours, more preferably 0.5 to 2 hours, and more preferably 1 hour.
[0051] In the present invention, the time for mixing and dispersing the surfactant and water is preferably 0.5 to 2 hours, more preferably 0.8 to 1.5 hours, and more preferably 1 hour.
[0052] In the present invention, the second dispersion liquid and the third dispersion liquid are sequentially added to the first dispersion liquid for dispersion for a time of preferably 2 to 10 hours, more preferably 4 to 8 hours, and even more preferably 5 hours.
[0053] In the present invention, the preparation method of nitrogen-sulfur co-doped graphene in step (2) preferably includes the following steps: mixing and dispersing graphene oxide with water to obtain a fourth dispersion; mixing and dispersing thiourea with water to obtain a fifth dispersion; adding the fifth dispersion to the fourth dispersion for dispersion; and subjecting the products obtained by the above dispersions to a hydrothermal reaction to obtain nitrogen-sulfur co-doped graphene.
[0054] In the present invention, in the fourth dispersion, the mass-to-volume ratio of graphene oxide to water is preferably 100-600 mg:15-100 mL, more preferably 200-500 mg:30-80 mL, and more preferably 300 mg:50 mL.
[0055] In the present invention, in the fifth dispersion, the mass-to-volume ratio of thiourea to water is preferably 500-1200 mg:5-50 mL, more preferably 600-1000 mg:10-30 mL, and even more preferably 900 mg:20 mL.
[0056] In the present invention, the mass ratio of the graphene oxide to the thiourea is preferably 1:1-10, more preferably 1:2-6, and more preferably 1:3.
[0057] In the present invention, the time for mixing and dispersing the graphene oxide and water, and the time for mixing and dispersing the thiourea and water are independently preferably 10 to 60 minutes, more preferably 15 to 40 minutes, and even more preferably 20 minutes.
[0058] In the present invention, the fifth dispersion liquid is added to the fourth dispersion liquid for dispersion for preferably 2 to 8 hours, more preferably 3 to 6 hours, and even more preferably 4 hours.
[0059] In the present invention, the temperature of the hydrothermal reaction is preferably 150-200° C., more preferably 160-200° C., and more preferably 180° C.; the time is preferably 6-15 h, more preferably 8-14 h, and more preferably 12 h.
[0060] In the present invention, the hydrothermal reaction preferably further comprises: cooling the hydrothermal product, and sequentially centrifugally washing and drying.
[0061] In the present invention, the reagents for the centrifugal washing are preferably water and ethanol; the number of centrifugal washings using water and the number of centrifugal washings using ethanol are independently preferably 2 to 6 times, more preferably 2 to 5 times, and more preferably 3 times.
[0062] In the present invention, the drying temperature is preferably 50 to 80° C., more preferably 55 to 70° C., and more preferably 60° C.; the drying time is preferably 8 to 24 h, more preferably 8 to 12 h, and more preferably 10 h.
[0063] In the present invention, the surfactant in step (2) preferably includes hexadecyltrimethylammonium bromide and / or polyvinylpyrrolidone, and more preferably hexadecyltrimethylammonium bromide. The surfactant can help form the morphology faster and better during the reaction process.
[0064] In the present invention, the mass ratio of the porous Fe3O4 nanospheres, the nitrogen-sulfur co-doped graphene and the surfactant in step (2) is preferably 9-36:12.5-50:0.5-2, further preferably 12-24:16-34:0.6-1.4, and more preferably 18:25:1.
[0065] In the present invention, the mixed and dispersed product obtained in step (2) preferably further comprises: centrifugal washing and drying in sequence before annealing.
[0066] In the present invention, the reagent for the centrifugal washing is preferably water; the number of the centrifugal washing is preferably 2 to 8 times, more preferably 3 to 5 times, and more preferably 3 times.
[0067] In the present invention, the drying temperature is preferably 50 to 80° C., more preferably 55 to 70° C., and more preferably 60° C.; the drying time is preferably 5 to 24 h, more preferably 6 to 12 h, and more preferably 10 h.
[0068] In the present invention, the protective atmosphere in step (2) is preferably nitrogen and / or argon, more preferably nitrogen.
[0069] In the present invention, the temperature of the annealing treatment in step (2) is preferably 350-1200°C, more preferably 500-1000°C, and more preferably 700°C; the time is preferably 0.5-4h, more preferably 0.8-2h, and more preferably 1h. The role of annealing treatment is to increase the crystallinity of the catalyst, eliminate impurities in the catalyst, and improve the conductivity of the catalyst.
[0070] In the present invention, the protective atmosphere in step (3) is preferably nitrogen and / or argon, and more preferably nitrogen.
[0071] In the present invention, the phosphorus source in step (3) preferably includes sodium hypophosphite and / or ammonium hypophosphite, and more preferably sodium hypophosphite.
[0072] In the present invention, the mass ratio of the nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material to the phosphorus source in step (3) is preferably 0.5-2:3-15, more preferably 0.8-1.5:5-10, and more preferably 1:5.
[0073] In the present invention, the temperature of the solid-state phosphating reaction in step (3) is preferably 270-450°C, more preferably 300-400°C, and more preferably 350°C; the time is preferably 1-4h, more preferably 1.5-3h, and more preferably 2h; the rate of heating to the desired solid-state phosphating reaction temperature is preferably 1-10°C / min, more preferably 3-7°C / min, and more preferably 5°C / min.
[0074] The present invention also provides a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material prepared by the preparation method.
[0075] The present invention also provides an application of the nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material as a water oxidation electrocatalyst.
[0076] In the present invention, the application method is not limited, and any method known to those skilled in the art may be used.
[0077] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0078] In an embodiment of the present invention, the ferric chloride is ferric chloride hexahydrate, and the cetyltrimethylammonium bromide is CTAB.
[0079] Example 1
[0080] This embodiment provides a method for preparing a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material, comprising the following steps:
[0081] (1) Under magnetic stirring, 10 mmol of ferric chloride hexahydrate and 88 mmol of sodium acetate were dissolved in 100 mL of a mixed solvent of ethylene glycol and diethylene glycol in a volume ratio of 1:4, and the dispersion was continued for 2 h. After being uniformly dispersed, the obtained uniform solution was transferred to a stainless steel autoclave lined with Teflon and heated at 200 °C for 8 h. The obtained product was washed with ethanol and water for 5 times in sequence to obtain porous Fe3O4 nanospheres, which were recorded as p-Fe3O4.
[0082] 300 mg of graphene oxide (GO, manufacturer STANDARD GRAPHENE, brand UGO469-191022) was dispersed in 50 mL of water and ultrasonically treated for 20 min to obtain a fourth dispersion; 900 mg of thiourea was dispersed in 20 mL of water and ultrasonically treated for 20 min to obtain a fifth dispersion; then, the fifth dispersion was injected into the fourth dispersion, and magnetic stirring was continued for 4 h to form a uniform mixed solution; then, the mixed solution was transferred to a hydrothermal reactor and reacted at 180 ° C for 12 h; after the reaction was completed, the product was naturally cooled to room temperature, washed by centrifugation with water and ethanol for 3 times, and dried at 60 ° C for 10 h to obtain black nitrogen-sulfur co-doped graphene, denoted as N,S-Gr;
[0083] (2) 36 mg p-Fe3O4 was dispersed in 40 mL water and subjected to ultrasonic treatment for 1 h to obtain a first dispersion; 50 mg N,S-Gr was dispersed in 60 mL water and subjected to ultrasonic treatment for 1 h to obtain a second dispersion; 2 mg CTAB was dispersed in 10 mL water and subjected to dispersion for 1 h to obtain a third dispersion; then, the second dispersion and the third dispersion were sequentially injected into the first dispersion, and magnetic stirring was continued for 5 h to form a uniform mixed solution; then, the dispersed product was washed three times by centrifugation with deionized water, dried at 60 ° C for 10 h, and then annealed at 700 ° C in a nitrogen atmosphere for 1 h to obtain a nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material, recorded as p-Fe3O4@N,S-Gr;
[0084] (3) p-Fe3O4@N,S-Gr and sodium hypophosphite were placed at both ends of a quartz boat in a mass ratio of 1:5 and heated to 350°C at a heating rate of 5°C / min under nitrogen protection for 2 h to obtain a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material, denoted as p-Fe3O4 / FeP@N,S-Gr.
[0085] The p-Fe3O4 obtained in step (1) of Example 1 and the p-Fe3O4 / FeP@N,S-Gr obtained in Example 1 were subjected to TEM detection. The results are as follows: Figure 1 shown. Figure 1 a in the figure is the TEM result of p-Fe3O4. The results show that there is a porous structure on the surface of the obtained Fe3O4 particles and the size of the particles is less than 100nm. Figure 1 Figures b and c are TEM results of p-Fe3O4 / FeP@N,S-Gr. The results show that the target catalyst has been successfully obtained and the p-Fe3O4 / FeP spheres are embedded in nitrogen-sulfur co-doped graphene.
[0086] Figure 2 This is the XRD pattern of p-Fe3O4 / FeP@N,S-Gr obtained in Example 1. Figure 2 The results show that the target catalyst p-Fe3O4 / FeP@N,S-Gr has characteristic peaks of Fe3O4 and FeP, which further proves that the Fe3O4 / FeP heterojunction is successfully obtained through the solid-state phosphating process. At the same time, the characteristic peaks of graphene are also confirmed.
[0087] Figure 3 These are the performance comparison test results of p-Fe3O4 obtained in step (1) of Example 1, p-Fe3O4@N,S-Gr obtained in step (2) of Example 1, and p-Fe3O4 / FeP@N,S-Gr obtained in Example 1 and commercial RuO2. Figure 3a in the figure is the OER polarization curve. The results show that the target catalyst p-Fe3O4 / FeP@N,S-Gr exhibits lower overpotential and higher activity. Figure 3 b is the value of 10, 50 and 100 mA / cm 2 The results show that the target product p-Fe3O4 / FeP@N,S-Gr has a lower overpotential and exhibits significant electrochemical activity. Figure 3 Where c is the Tafel slope. The results show that the target product p-Fe3O4 / FeP@N,S-Gr exhibits a lower Tafel slope, indicating that the target electrocatalyst has higher electrocatalytic reaction kinetics.
[0088] Figure 4 The electrochemical impedances of p-Fe3O4 obtained in step (1) of Example 1, p-Fe3O4@N,S-Gr obtained in step (2), and p-Fe3O4 / FeP@N,S-Gr obtained in Example 1. The results show that the target catalyst p-Fe3O4 / FeP@N,S-Gr exhibits lower electrochemical impedance, further indicating that the construction of the heterojunction of p-Fe3O4 and FeP can significantly enhance the migration of carriers and accelerate the electrochemical reaction, thereby improving the reaction efficiency.
[0089] Figure 5 The theoretical simulation of the delocalization of the charge distribution at the Fe3O4 / FeP heterojunction interface obtained in Example 1 significantly enhancing the catalyst activity and conductivity shows that the construction of the heterojunction causes the migration of interface carriers and the redistribution of charges.
[0090] Example 2
[0091] This embodiment provides a method for preparing a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material, comprising the following steps:
[0092] (1) Under magnetic stirring, 5 mmol of ferric chloride hexahydrate and 44 mmol of sodium carbonate were dissolved in 80 mL of a mixed solvent of ethylene glycol and diethylene glycol in a volume ratio of 1:4, and the dispersion was continued for 4 h. After being uniformly dispersed, the obtained uniform solution was transferred to a Teflon-lined stainless steel autoclave and heated at 160°C for 16 h. The obtained product was washed with ethanol and water for 4 times in sequence to obtain porous Fe3O4 nanospheres, which were recorded as p-Fe3O4.
[0093] 400 mg of graphene oxide (GO, manufacturer STANDARD GRAPHENE, brand UGO469-191022) was dispersed in 60 mL of water and ultrasonically treated for 40 min to obtain a fourth dispersion; 1200 mg of thiourea was dispersed in 50 mL of water and ultrasonically treated for 40 min to obtain a fifth dispersion; then, the fifth dispersion was injected into the fourth dispersion, and magnetic stirring was continued for 6 h to form a uniform mixed solution; then, the mixed solution was transferred to a hydrothermal reactor and reacted at 180 ° C for 8 h; after the reaction was completed, the product was naturally cooled to room temperature, washed twice by centrifugation with water and ethanol respectively, and dried at 70 ° C for 12 h to obtain black nitrogen-sulfur co-doped graphene, recorded as N,S-Gr;
[0094] (2) 30 mg p-Fe3O4 was dispersed in 50 mL water and subjected to ultrasonic treatment for 2 h to obtain a first dispersion; 40 mg N,S-Gr was dispersed in 70 mL water and subjected to ultrasonic treatment for 2 h to obtain a second dispersion; 1 mg CTAB was dispersed in 5 mL water and subjected to dispersion for 2 h to obtain a third dispersion; then, the second dispersion and the third dispersion were sequentially injected into the first dispersion, and magnetic stirring was continued for 10 h to form a uniform mixed solution; then, the dispersed product was washed five times by centrifugation with deionized water, dried at 50 °C for 24 h, and then annealed at 900 °C in an argon atmosphere for 0.5 h to obtain a nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material, denoted as p-Fe3O4@N,S-Gr;
[0095] (3) p-Fe3O4@N,S-Gr and ammonium hypophosphite were placed at both ends of a quartz boat in a mass ratio of 0.5:3 and heated to 350°C at a heating rate of 3°C / min under argon protection for 3 h to obtain a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material, denoted as p-Fe3O4 / FeP@N,S-Gr.
[0096] Example 3
[0097] This embodiment provides a method for preparing a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material, comprising the following steps:
[0098] (1) Under magnetic stirring, 20 mmol of ferric chloride hexahydrate and 176 mmol of sodium carbonate + sodium citrate (the molar ratio of sodium carbonate to sodium citrate is 3:2) were dissolved in 150 mL of a mixed solvent of ethylene glycol and diethylene glycol in a volume ratio of 1:4, and the dispersion was continued for 2 h. After being uniformly dispersed, the obtained uniform solution was transferred to a Teflon-lined stainless steel autoclave and heated at 220 °C for 6 h. The obtained product was washed with ethanol and water for 5 times in sequence to obtain porous Fe3O4 nanospheres, which were recorded as p-Fe3O4.
[0099] 200 mg of graphene oxide (GO, manufacturer STANDARD GRAPHENE, brand UGO469-191022) was dispersed in 60 mL of water and ultrasonically treated for 15 min to obtain a fourth dispersion; 600 mg of thiourea was dispersed in 30 mL of water and ultrasonically treated for 15 min to obtain a fifth dispersion; then, the fifth dispersion was injected into the fourth dispersion, and magnetic stirring was continued for 4 h to form a uniform mixed solution; then, the mixed solution was transferred to a hydrothermal reactor and reacted at 160° C. for 15 h; after the reaction was completed, the product was naturally cooled to room temperature, washed by centrifugation with water and ethanol for 4 times, and dried at 80° C. for 8 h to obtain black nitrogen-sulfur co-doped graphene, denoted as N,S-Gr;
[0100] (2) 18 mg p-Fe3O4 was dispersed in 30 mL water and subjected to ultrasonic treatment for 0.5 h to obtain a first dispersion; 25 mg N,S-Gr was dispersed in 40 mL water and subjected to ultrasonic treatment for 0.5 h to obtain a second dispersion; 1 mg CTAB was dispersed in 8 mL water and subjected to dispersion for 0.5 h to obtain a third dispersion; then, the second dispersion and the third dispersion were sequentially injected into the first dispersion, and magnetic stirring was continued for 2 h to form a uniform mixed solution; then, the dispersed product was centrifugally washed twice with deionized water, dried at 80 ° C for 8 h, and then annealed at 600 ° C in a nitrogen atmosphere for 4 h to obtain a nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material, recorded as p-Fe3O4@N,S-Gr;
[0101] (3) p-Fe3O4@N,S-Gr and sodium hypophosphite were placed at both ends of a quartz boat in a mass ratio of 1.5:10 and heated to 400°C at a heating rate of 7°C / min under nitrogen protection for 1 h to obtain a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material, denoted as p-Fe3O4 / FeP@N,S-Gr.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a nitrogen-sulfur co-doped graphene-modified porous iron oxide / phosphide heterojunction nanocomposite material, characterized in that: The following steps are involved: (1) mixing an iron source, an alkaline salt and an organic solvent to perform a solvothermal reaction to obtain porous Fe3O4 nanospheres; (2) mixing and dispersing the porous Fe3O4 nanospheres, nitrogen-sulfur co-doped graphene, surfactant and water described in step (1); annealing the mixed and dispersed product under a protective atmosphere to obtain a nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material; (3) Under a protective atmosphere, subjecting the nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material described in step (2) to a solid-state phosphating reaction with a phosphorus source to obtain a nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the iron source includes ferric chloride and / or ferric nitrate; the alkaline salt includes one or more of sodium acetate, sodium carbonate and sodium citrate; the organic solvent is a mixture of ethylene glycol and diethylene glycol, and the volume ratio of ethylene glycol to diethylene glycol is 0.5-2:2-8.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the molar ratio of the iron source to the alkaline salt is 0.5-2:4.4-17.6, and the molar to volume ratio of the iron source to the organic solvent is 0.5-2 mmol:5-20 mL.
4. The preparation method according to claim 3, characterized in that: In step (1), the temperature of the solvent thermal reaction is 150 to 240° C. and the time is 4 to 16 hours.
5. The preparation method according to claim 1, characterized in that: In step (2), the surfactant includes hexadecyltrimethylammonium bromide and / or polyvinylpyrrolidone; the mass ratio of the porous Fe3O4 nanospheres, the nitrogen-sulfur co-doped graphene and the surfactant is 9-36:12.5-50:0.5-2.
6. The preparation method according to claim 1 or 5, characterized in that: In step (2), the annealing treatment is carried out at a temperature of 350 to 1200° C. and for a time of 0.5 to 4 hours.
7. The preparation method according to claim 1, characterized in that: In step (3), the phosphorus source includes sodium hypophosphite and / or ammonium hypophosphite; the mass ratio of the nitrogen-sulfur co-doped graphene modified porous Fe3O4 nanocomposite material to the phosphorus source is 0.5-2:3-15.
8. The preparation method according to claim 1 or 7, characterized in that: In step (3), the temperature of the solid-state phosphating reaction is 270-450° C., the time is 1-4 hours, and the rate of heating to the desired solid-state phosphating reaction temperature is 1-10° C. / min.
9. Nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nitrogen-sulfur co-doped graphene modified porous iron oxide / phosphide heterojunction nanocomposite material as claimed in claim 9 as a water oxidation electrocatalyst.